Europol 25, Hungary 20 - Mátyás Hegyaljai (Belügyi Szemle)
Aim: Europol has evolved over the last quarter of a century, as its legal framework has changed in line with EU requirements, and its tasks have expanded and its network of contacts has become more extensive.